PERANCANGAN BUKU CERITA BERGAMBAR PERMAINAN TRADISIONAL ANAK-ANAK KABUPATEN KERINCI - IZWAN JAILANI, Ir. Drs. Heldi, M.Si., Ph,.D. Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Thirteen years ago there was a phenomenon where traditional games in the Kerinci Regency began to be rarely played and began to disappear while children today don’t even know some of the traditional Kerinci games due to lack of information.The aim of the designer is to design a Kerinci Regional Traditional Game book optimally for information about traditional games for children, through informative and communicative picture books as a source of knowledge in the Kerinci Regency and to add a collection of books on the traditional district games.The method used in the design of a picture story book uses a combination of rational and systematic glass box methods and a 4-D model that includes the stages of define, design, develop, and disseminate and analysis of 5W + 1H data which is used as the basic concept of problem solving.This design produced a draft of the Kerinci Regional Traditional Picture Book as the main media and was supported by several media: x-banners, posters, stickers, phleg chains, bookmarks, pins, totebags, and calendars.Keywords: Book, Picture, Game, Kerinci, Traditional.